Validity and reliability of the Indonesian version of the new brief job stress questionnaire (short version) for work-related stress screening among office workers (Faculty of Medicine Universitas Indonesia, 2022)
BACKGROUND The short version of the new brief job stress questionnaire (SV-NBJSQ) that is originally in Japanese could evaluate work-related stress in Indonesian office workers. However, it has not been validated in Indonesian. Thus, this study aimed to test the validity and reliability of the Indonesian version of the SV-NBJSQ. METHODS This study was conducted by linguistic and cultural adaptation of the original Japanese questionnaire into Indonesian and continued with exploratory factor analysis, internal consistency, and reliability test of Cronbach’s alpha. Electronic and paper-based data were collected using total sampling from office workers at two companies in Jakarta from December 2017 to August 2018. RESULTS A total of 438 respondents filled the questionnaire. The final version of the questionnaire consisted of 63 items, screened based on a loading factor of >0.4 and 13 factors (dimensions). Each factor had a Cronbach’s alpha of 0.628–0.887, while the entire 63 had 0.904 with a total documented cumulative variation of 64.97%. CONCLUSIONS The Indonesian version of the SV-NBJSQ is valid and reliable. Thus, we may use it as a more suitable, updated, and comprehensive tool to evaluate work-related stress among office workers.